2000
DOI: 10.1016/s0370-2693(00)00146-5
|View full text |Cite
|
Sign up to set email alerts
|

A simple proof of the non-renormalization of the Chern–Simons coupling

Abstract: We give a very simple proof that the renormalization of the Chern-Simons coupling in the Wilsonian effective action is exhausted at one-loop. Our proof can apply to arbitrary 2+1-dimensional abelian as well as nonabelian gauge theories without a bare Chern-Simons coupling, including any non-renormalizable interactions and non-minimal couplings. Our proof reveals that small (but not large) gauge invariance is enough to ensure the absence of higher order corrections.1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(37 reference statements)
1
5
0
3
Order By: Relevance
“…We showed that the ChernSimons term does not receive any one-loop correction, even a finite one. Moreover, we can conclude, due to a non-renormalization theorem of the Chern-Simons coupling [24][25][26], that it does not receive any higher order corrections, and therefore the gauge (Chern-Simons) sector of the model is UV finite and free of UV/IR mixing to all loop orders.…”
Section: Effective Actionmentioning
confidence: 81%
“…We showed that the ChernSimons term does not receive any one-loop correction, even a finite one. Moreover, we can conclude, due to a non-renormalization theorem of the Chern-Simons coupling [24][25][26], that it does not receive any higher order corrections, and therefore the gauge (Chern-Simons) sector of the model is UV finite and free of UV/IR mixing to all loop orders.…”
Section: Effective Actionmentioning
confidence: 81%
“…Supersymmetry is a symmetry under which the Lagrangian is invariant up to a total derivative. It is interesting to note that an argument similar to that of the non-renormalization theorem is possible for three dimensional Chern-Simons theory, 15) which is again gauge invariant up to a total derivative.…”
Section: Remarksmentioning
confidence: 99%
“…En cuanto a las correcciones perturbativas, para el caso abeliano [30] como para el no abeliano [31], [32] se ha probado que el coeficiente del término de Chern-Simons no se renormaliza a todo orden en teoría de perturbaciones.…”
Section: La Anomalía De Paridadunclassified
“…En particular, dado que en ese caso el coeficiente del termino de Chern-Simons debe estar cuantizado, la invarianza de gauge de la teoría efectiva frente a transformaciones grandes exige que este coeficiente no se renormalice. Sin embargo, la versión no abeliana del teorema de Coleman-Hill fue demostrada sólo recientemente usando el método de holomorficidad de Seiberg [31], y por métodos mas directos en [32]. Estos resultados han sido extendidos en parte al presente caso no conmutativo en [77].…”
Section: Alcances Y Limitaciones Del Cálculounclassified
See 1 more Smart Citation